Wastewater Removal Pollutants Using Polyethylene terephthalate Media : Moving Bed Biofilm Reactor - Muliyadi, Muliyadi; Purwanto, Purwanto; Sumiyati, Sri; Budiyono, Budiyono; Sudarno, Sudarno; Warsito, Budi (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2025)
The increasing wastewater necessitates innovative wastewater treatment methods, such as anaerobic MBBR with PET as media, which enhance microbial degradation and biofilm formation. The aim was to analyze the rate of degradation kinetics in anaerobic MBBR reactors for biological wastewater treatment. This research examined three factors: the BOD, COD, and TSS. Domestic wastewater was used in this study. The reactor measured 40 × 40 × 50 cm and had a thickness of 4 mm. The construction was performed using glass material. The operation was performed for 30 days. Microorganisms grew and reproduced on the surface of the plastic bottle cap media during the anaerobic bioreactor seeding process by adding as many local microorganisms as 1.6/70 liters of wastewater. The study revealed that domestic wastewater used for wastewater treatment has BOD, COD, TSS, Ammonia, and Fat contents that exceed the set threshold value. The BOD/COD ratio was 0.55. After acclimatization, the biofilm was fully developed, effectively removing organic contaminants and producing fungal polysaccharides. In conclusion, the study of substrate concentration and degradation kinetics is crucial for system design and operation, emphasizing the need for substrate optimization to enhance microbial activity.